1996
DOI: 10.1212/wnl.47.1.196
|View full text |Cite
|
Sign up to set email alerts
|

A newly identified polymorphism in the apolipoprotein E enhancer gene region is associated with Alzheimer's disease and strongly with the epsilon 4 allele

Abstract: Apolipoprotein E allele 4 (apoE epsilon 4) is a major risk factor for late-onset AD. Inheritance of this allele is associated with an earlier age of onset of dementia in individuals with AD. It is unknown whether other polymorphisms in the apoE gene may influence the effect of apoE epsilon 4 on AD. We screened portions of the promoter enhancer element and of the apoE receptor binding domain for other polymorphisms that could affect risk of AD. In particular, a C/G polymorphism at position +113 of the apoE mRNA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
36
0

Year Published

1999
1999
2008
2008

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(38 citation statements)
references
References 13 publications
2
36
0
Order By: Relevance
“…An enhancer sequence has also been identified in intron 1 of APOE, and a variant at position 1163 was found in this region as well (Fig. 1b;Mui et al 1996). Although both of these sites lie in regulatory regions, neither is located in one of the mapped protein-binding sequences identified in APOE (Fig.…”
Section: Apoe Sequence Variants In the Core Samplementioning
confidence: 81%
See 2 more Smart Citations
“…An enhancer sequence has also been identified in intron 1 of APOE, and a variant at position 1163 was found in this region as well (Fig. 1b;Mui et al 1996). Although both of these sites lie in regulatory regions, neither is located in one of the mapped protein-binding sequences identified in APOE (Fig.…”
Section: Apoe Sequence Variants In the Core Samplementioning
confidence: 81%
“…; J. Stengård, in prep.) A number of recent studies have focused attention on SNPs in the 5Ј flanking region of APOE that could alter gene expression and be involved in the phenotypic associations with Alzheimer's disease and CVD risk (Mui et al 1996;Artiga et al 1998a,b;Bullido et al 1998;Lambert et al 1998a,b;Lambert et al 2000). Several of these SNPs, known as -491A/T (position 560) and -427 C/T (position 624), have been associated with an increased risk of Alzheimer's disease that is independent of the 4 status of the individual (Artiga et al 1998a,b;Bullido et al 1998;Martin et al 2000).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has earlier been shown that the region between ϩ44 and ϩ262 (IRE1) has enhancer activity, 24 but the ϩ113 allelic status in that study is unknown because the SNP was identified almost 10 years later. 25 We studied the enhancer activity using a smaller 50-bp region (from ϩ89 to ϩ138) of the first intron region in the APOE gene. Our transcription experiments showed that primarily the ϩ113C allele has an effect on the luciferase gene expression, mainly acting as a transcriptional enhancer.…”
Section: Apoe ؉113g/c Snp Region Can Act As An Enhancermentioning
confidence: 99%
“…Another SNP of APOE, -219G/T, located in the promoter of APOE, was reported to be significantly associated with APOE promoter activity, apoE plasma concentration, and CAD (7,8,10). In addition, the 113G/C SNP of APOE may be relevant for APOE regulation because of its location in the APOE intron-1 enhancer element that constitutes a binding site for specific nuclear protein factors (15,16).…”
mentioning
confidence: 99%